Meningkatkan Penalaran Statistik melalui Mengerjakan Soal Latihan Secara Aktif pada Mahasiswa Kesehatan Masyarakat Universitas Airlangga - Indawati, Rachmah; Qomaruddin, Mochammad Bagus; Rachmayanti, Riris Diana (Penerbit Goodwood, 2024)
Purpose: Statistical reasoning is the way people reason with ideas, relate one concept to another, and can interpret statistical results. Doing tasks actively to develop cognitive abilities. The aim is to build statistical reasoning so that participants can explore data, be able to see data as aggregates, how to organize and interpret results. Methodology: The form of activity is to provide training through giving exercise/doing assignments that require active participants to develop cognitive abilities. a model of cognitive development that incorporates statistical processes. Results: Ability to explain data, most have difficulty reasoning about different data. The average is 64.44. The training results showed that there was understanding in explaining data in different situations, the average is 71.85. The ability to organize data shows that participants have knowledge about how to observe data according to statistical procedures. The average value is 76.67. Data presentation skills show that participants can display and interpret data. The average is 78.89. Conclusions: Participants have an average ability in explaining data, organizing data, and presenting data. Learning statistical concepts requires statistical practice, which takes a considerable amount of time for learning. This reasoning process provides participants with the opportunity to develop their statistical knowledge. Statistical reasoning should be continuously applied to students, as they constantly encounter dynamic data. Limitations: Since the study is focused on a specific geographic area (Gurabati Subdistrict)4, the findings may not be directly applicable to other regions with different urban planning, waste collection practices, or traffic conditions. Contribution: The results of the assignment concluded that the practice of analyzing data influenced the participants' knowledge insight.